HAPPY HOUSE SEBAGAI SARANA EDUKASI DAN KONSELING BAGI MASYARAKAT KAMPUNG GILA DAERAH PONOROGO - Solekah, Darus; Elyana, Devika; Sunarsih, Iis Sri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Crazy village is one of regions take place in Ponorogo. In which, there are many crazy citizenries there. The disease of crazy will give bad impact to the childrenâs education. The purpose of this program is to improve childrenâs interest and achievement in crazy village by giving study guidance and counseling. The methodes of doing this program are done by giving study mentoring and counseling. The results of this program are that Happy House give positive impact to the childrenâs interest and achievement. By giving counseling program, it makes the studentâs character be better, make them more confident and improve the studentâs social interaction besides counseling program can motivate the students to reach their biggest wish and prepare their future life.